Investigating the influence of firm characteristics on the ability to exercise market power: A stochastic frontier analysis approach with an application to the iron ore market - Robert Germeshausen; Timo Panke; Heike Wetzel (Institute of Energy Economics at the University of Cologne (EWI), 2014)
This paper empirically analyzes the existence of market power in the global iron ore market during the period 1993-2012 using an innovative Stochastic Frontier Analysis approach introduced by Kumbhakar et al. (2012). In contrast to traditional econometric procedures, this approach allows for the estimation of firm- and time-specific Lerner indices and, therefore, the assessment of the influence of individual firm characteristics on the ability to generate markups. We find that markups on average amount to 20%. Moreover, location and experience are identified to be the most important determinants of the magnitude of firm-specific markups.
Keywords: D22; L11; L72; 330; Estimation of market power; Lerner indices; Stochastic Frontier Analysis; Non-renewable resources